Pengaruh Persepsi Kesejahteraan Guru dan Pengalaman PLP Terhadap Minat Menjadi Guru pada Mahasiswa FKIP Universitas Sebelas Maret Angkatan 2020 - Krisnawati Krisnawati; Siswandari Siswandari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to determine (1) the influence of perceptions about teacher welfare on interest in becoming teachers among FKIP UNS students; (2) the influence of PLP experience on interest in becoming a teacher among FKIP UNS students; and (3) the influence of perceptions about teacher welfare and PLP experience on interest in becoming teachers among FKIP UNS students. This research is quantitative research. The sampling technique is simple random sampling. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear regression. The research results showed that perceptions of teacher welfare and PLP experience significantly influenced interest in becoming a teacher. This is shown by the acquisition of F = 104.05 with a significance value of 0.0000 <0.05. The regression line function equation model for these three variables is Y = 7.394 + 0.020X1 + 0.527X2. The simultaneous influence of teacher welfare perceptions and PLP experience on interest in becoming a teacher is 39.6%.